A first-generation X-inactivation profile of the human X chromosome - Carrel, Laura (The National Academy of Sciences, 1999)
In females, most genes on the X chromosome are generally assumed to be transcriptionally silenced on the inactive X as a result of X inactivation. However, particularly in humans, an increasing number of genes are known to “escape” X inactivation and are expressed from both the active (Xa) and inactive (Xi) X chromosomes; such genes reflect different molecular and epigenetic responses to X inactivation and are candidates for phenotypes associated with X aneuploidy. To identify genes that escape X inactivation and to generate a first-generation X-inactivation profile of the X, we have evaluated the expression of 224 X-linked genes and expressed sequence tags by reverse-transcription–PCR analysis of a panel of multiple independent mouse/human somatic cell hybrids containing a normal human Xi but no Xa. The resulting survey yields an initial X-inactivation profile that is estimated to represent ≈10% of all X-linked transcripts. Of the 224 transcripts tested here, 34 (three of which are pseudoautosomal) were expressed in as many as nine Xi hybrids and thus appear to escape inactivation. The genes that escape inactivation are distributed nonrandomly along the X; 31 of 34 such transcripts map to Xp, implying that the two arms of the X are epigenetically and/or evolutionarily distinct and suggesting that genetic imbalance of Xp may be more severe clinically than imbalance of Xq. A complete X-inactivation profile will provide information relevant to clinical genetics and genetic counseling and should yield insight into the genomic and epigenetic organization of the X chromosome.